Literary and non-literary responses towards 9/11
1 online resource.
Keywords: "This book presents a range of analytical responses towards 9/11 through a critical review of its literary, non-literary and cultural representations. It examines the ways in which this event has shaped and complicated the relationship between various national and religious identities in contemporary world history. Unlike earlier studies on the topic, this work reconciles both eclectic and pragmatic approaches by analyzing the stereotypes of nationhood and identities as also by questioning theoretical concepts in the context of latest political developments. The chapters focus on discourses, themes, imagery and symbolism from across fiction and non-fiction, films, art, music, and political movements. The volume addresses complexities arising within different local contexts (e.g., Hunza and state development); surveys broader frameworks in South Asia (representation of Muslims in Bollywood films); and gauges international impact (US drone attacks in Islamic countries; treatment meted out to Muslims in Europe). It also connects these with relevant theory (e.g., Orientalism) and policy perspectives (e.g. Patriotic Act). The authors further discuss consequences for minorities and marginalization, cultural relativism vs ethnocentrism, clash of civilizations, fundamentalism, Islamization and post-9/11 'Islamophobia'. This book will be useful to scholars and researchers of South Asian literature, Islamic studies, literary criticism, political sociology, sociology and cultural studies, those in media and the interested general reader"--